Factors contributing to the uptake of childhood vaccination in Galkayo District, Puntland, Somalia - Mohamed Farah Abdullahi; Jennifer Stewart Williams; Klas-Göran Sahlèn; Khalif Bile; John Kinsman (Taylor & Francis Group, 2020)
Background As in many Sub-Saharan African countries, the health system in Somalia is not operating at the capacity needed to lift childhood vaccination coverage to ninety percent or above, as recommended by United Nations Children's Fund. Current national estimates of coverage for the six major vaccine preventable childhood diseases range from thirty to sixty percent. Infectious disease outbreaks continue to pose significant challenges for the country's health authorities. Objective This important qualitative study, conducted in Galkayo District, Somalia, investigates limiting factors associated with childhood vaccination uptake from the perspective of both communities and health care workers. Methods Qualitative information was collected through six focus group discussions with parents (n = 48) and five one-to-one interviews with health workers (n = 15) between March and May 2017, in three settings in the Galkayo District - Galkayo city, Bayra and Bacadwayn. Results From a health system perspective, the factors are: awareness raising, hard to reach areas, negative attitudes and perceived knowledge of health workers, inadequate supplies and infrastructure, and missed vaccination opportunities. From the perspective of individuals and communities the factors are: low trust in vaccines, misinterpretation of religious beliefs, vaccine refusals, Somalia's patriarchal system and rumours and misinformation. Parents mostly received immunization information from social mobilizers and health facilities. Fathers, who are typically family decision-makers, were poorly informed. The findings highlight the need for in-service training to enable health workers to improve communication with parents, particularly fathers, peripheral communities and local religious leaders. Conclusions Enhancing knowledge and awareness of vaccination among parents is crucial. Fathers' involvement is lacking. This may be boosted by highlighting fathers' obligation to protect their children's health through vaccination. It is also important that men engage with the wider community in decision-making and advance towards the global vaccination targets.